The Correlation Between Students' Introverted and Extroverted Personality Types and Their Speech Error Probability - Febrianti, Della; Kweldju, Siusana; Zen, Evynurul Laily (JOLLT Journal of Languages and Language Teaching, 2025)
Speaking is often considered as complex compared to the other three language skills. When engaged in speaking, individuals must produce speech in a limited timeframe, resulting in a brief gap between understanding words and verbalizing them. Consequently, speech errors remain common. Several factors may attribute to the speech errors occurrence, including the affective factor of personality. The present study aims to explore the correlation between students' personalities, specifically introverts and extroverts, and their speech error probability. A descriptive quantitative design and correlational method were employed, involving 26 undergraduate students of the English Education Department at Universitas Islam Darul ‘Ulum Lamongan, enrolled in a Speaking for Academic Purposes course. The Eysenck Personality Inventory (EPI) was utilized as the primary instrument, along with oral test of speech errors following the theory proposed by Clark and Clark (1977). Pearson Product-Moment Correlation analysis revealed a significance (2-tailed) value of 0.836 (>0.05), indicating no statistically significant correlation between personality type and speech error frequency. The correlation coefficient of -0.043 further suggested a weak negative relationship. These findings contribute to psycholinguistic research in EFL contexts by suggesting that personality traits, while influential in broader communicative behavior, may not directly impact students' linguistic processing accuracy in oral tasks. This insight supports the idea that effective spoken communication in EFL learning can be achieved regardless of individual personality types. Future studies are encouraged to expand the sample size and include more diverse student populations to validate and extend these findings.